Experimental Investigation on the Flexural Behavior of Composite Floor Panels Made of Cold-formed Steel and Timber for Sustainable Construction - DANDASHI, SEIFALDEEN ALAHNAF (2023)
Composite floor made of timber and steel have gained popularity and extensive application in the construction sector over the past few years. Unlike concrete-steel composites, the composite behaviour between timber and steel is not fully explored. This research investigates experimentally the flexural behavior of three full-scale specimens composed of cold-formed double cee joists connected to laminated veneer lumber using self-tapping screws. Each specimen in the set has a different screw spacing, and the degree of shear interaction was assessed by subjecting the samples to four-points loading. The deformed shapes were described, and the displacement at the midspan was plotted against the applied load. Accordingly, the initial stiffness was calculated and validated against the predictive theoretical models available in the literature. Moreover, the conformity of the proposed system was verified against the deflection and vibration criteria available in the relevant standards. Finally, the environmental impact of implementing the suggested system was evaluated by calculating the upfront carbon. The result were discussed with respect to the outputs of a benchmark reflects the conventional construction practice. As a conclusion, the proposed system adequately fulfils the strength and stiffness criteria for domestic buildings, and significantly reduces the GHG emissions attributed to construction sector.